(untitled) (Experimental biology, 2015)
The discovery of a minor cell population in tumors with features of tissue stem cells, which are called cancer stem cells (CSCs), has led to a new paradigm of cancerogenesis. According to this notion, many cancers (if not all) arise from CSCs, which renew themselves by asymmetric division (hierarchical model of cancerogenesis). A hierarchical model is distinct from a stochastic model, as the former is based on tumors arising not just from any tumor cell, but rather only from CSCs. The CSC concept bears answers to the most fundamental question of oncology, namely, how cancer cells relapse and metastasize after aggressive treatments including surgery and chemo- and radiotherapy. Therefore, understanding the biology of CSCs will open new avenues for cancer risk assessment, early detection, and prognostication as well as for developing new strategies for cancer prevention and therapies. Открытие минорной клеточной популяции в опухоли со свойствами тканевых стволовых клеток, названной раковыми стволовыми клетками (РСК), привело к новой парадигме канцерогенеза. Согласно этому представлению, многие виды рака (если не все) возникают из РСК, которые самообновляются путем асимметричного деления (иерархическая модель канцерогенеза). Иерархическая модель отличается от стохастической, поскольку первая основана на возникновении опухоли не из любой опухолевой клетки, а только из РСК. Концепция РСК дает ответы на большинство фундаментальных вопросов онкологии, например, как опухоли рецидивируют и метастазируют после энергичного лечения, включая хирургию и химио- и радиотерапию. Поэтому понимание биологии РСК откроет новые перспективы оценки риска, ранней диагностики и прогноза опухолевой прогрессии, а также разработки новых стратегий предотвращения и терапии рака.